PENGARUH PROJECT BASED LEARNING DALAM MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR MAHASISWA PADA MATERI HIDROKARBON - Lily Budinurani (Bajang Institute, 2025)
One of the learning that can generate student activity and independence is project based learning. This study aims to determine the effectiveness of project based learning on the achievement of learning outcomes and student character on hydrocarbon material. This type of research is experiment with posttest-only control design. Students of Teknik Otomotif Politeknik Baja Tegal are samples in this research. Random sampling technique is used for gathering sample. The independent variable of research is the level of implementation of project based learning while the dependent variable is students’ learning achievement and their character. The result of the difference test of the post-test value average shows that the average post-test of the experimental class is better than the control class. The final score average of the experimental class is higher than the control class i.e. the experimental class is 80 and the learning completeness reaches 90% while the average final score of the control class is 78 and the learning completeness is only 86%. The result of N-Gain test shows that there is an improvement between before treatment (pre-test) with after treatment (post-test) which is the class using the average project improvement of 0.72 on the high criteria while in the control class only 0.69 on medium criteria. Based on the result, it can be concluded that project based learning has an effect on students’ learning achievement and their character on the material of solution and gets positive response from students